THE MYTH OF METAPHOR SYMBOLS IN SPEECH I HAVE A DREAM - Zakaria, Zakaria; Hasyim, Muh; Tundreng, Syarifuddin (English Review: Journal of English Education, 2022)
The speech I Have A Dream is Martin Luther King's political speech, delivered in front of the Lincoln Memorial on August 28, 1963. In the text of speech there are several metaphorical symbols (language style) in conveying his message and protest attitude against the American legal and political system which is considered unfair. To fully understand the meaning and message of the speech, the research question is "What is the meaning of the mythical metaphorical symbol in Martin Luther King’s I Have A Dream?" In analyzing the metaphorical symbols in the speech, the researcher used Roland Barthes' semiotic approach and the research procedure used descriptive qualitative form. The results of this study found that the metaphorical symbols in I Have A Dream's speech used various syntactic patterns, namely: 1) using adjective word patterns such as symbolic shadow, beacon light, flames of withering, long night; 2) using noun patterns such as manacles, chains, island, ocean, languished, land, shameful, valley, hill, mountain, crooked place; 3) use a verb pattern as in the phrase to blow off steam, a rude awakening, returns to business